Quality of wheat grains harvested with different moisture contents and stored in hermetic and conventional system. (January 2018) - Scariot, Maurício Albertoni; Radünz, Lauri Lourenço; Dionello, Rafael Gomes; Toni, Josiel Ricardo; Mossi, Altemir José; Reichert Júnior, Francisco Wilson
Abstract: Wheat ( Triticum aestivum ) is one of the main cereals consumed in the world and is very important for food security. Harvest time and storage may influences physical and physiological quality, and also the fungal incidence in the grains. This work evaluated physical and physiological quality and fungal incidence in wheat grains of BRS Parrudo cultivar wheat at different harvest moisture contents and stored under hermetic and conventional conditions, PET bottles and kraft paper bags, respectively. Harvesting was done when wheat reached moisture contents (MCs) of 28.6, 18.5 and 12.9%, followed by drying at 38°C in a forced air circulation oven until MC was 13%. The wheat was then stored for 240 days. Quality evaluations were done after drying and every 60 days during the storage period. The quality of the wheat declined throughout the storage period, regardless of the MC, and harvest delay negatively affected quality. Fusarium spp. and other fungi declined while Aspergillus spp. and Penicillium spp. increased regardless of harvest MC or storage. Highlights: The influence of the harvest moisture content and the storage system on quality of wheat grains was evaluated. Harvesting wheat grain with the moisture content of 13% provide grains with low quality. Hermetic storage provides good conservation of the wheat grains over time. The contamination of Fusarium spp. is reduced during storage of wheat grains, but not fully. Grains stored in hermetic system showed lower contamination by Aspergillus spp. and Penicillium spp.